2019
DOI: 10.3389/fmicb.2019.02663
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacillus velezensis on Aeromonas veronii-Induced Intestinal Mucosal Barrier Function Damage and Inflammation in Crucian Carp (Carassius auratus)

Abstract: Aeromonas veronii is an emerging aquatic pathogen causing hemorrhagic septicemia in humans and animals. Probiotic is an effective strategy for controlling enteric infections through reducing intestinal colonization by pathogens. Here we report that the consumption of Bacillus velezensis regulated the intestinal innate immune response and decreased the degree of intestinal inflammation damage caused by the A. veronii in Crucian carp. In this study, we isolated four strains of B. velezensis, named C-11, S-22, L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 91 publications
(98 reference statements)
1
23
0
Order By: Relevance
“…IgM that was produced by plasma cells was an important indicator of sh-speci c immunity, it participated in the immune cycle of the sh and played a vital role in the process (Zhang et al 2019), the increased expression of IgM indicated that the grass carp's immune system was activated (Bilal et al 2016;Kole et al 2019). IL-1β and IL8 were the two main pro-in ammatory cytokines, which played an important role in triggering the in ammatory response against bacterial and viral infections (Reis et al 2012;Wang et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IgM that was produced by plasma cells was an important indicator of sh-speci c immunity, it participated in the immune cycle of the sh and played a vital role in the process (Zhang et al 2019), the increased expression of IgM indicated that the grass carp's immune system was activated (Bilal et al 2016;Kole et al 2019). IL-1β and IL8 were the two main pro-in ammatory cytokines, which played an important role in triggering the in ammatory response against bacterial and viral infections (Reis et al 2012;Wang et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…discovered that feeding Bacillus velezensis can promote the expression of interleukin 1β (IL-1β) and protect sh from A.veronii infection (Zhang et al 2019). In addition, common immune factors also included lysozyme (LSZ), complement C3 (C3) and IL8.…”
Section: Introductionmentioning
confidence: 99%
“…Our study concurs with a previous study that showed that the supplementation of B. velezensis ‐induced immune responses by upregulating the expression levels of immune‐related genes such as IL‐1β , IFN‐γ and TNF‐α in the gut and head kidney of Crucian carp (Zhang et al . 2019). Several studies have also reported that probiotic administration of B. subtilis significantly upregulates the expression levels of IFN‐γ in broiler chickens (Liu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Still, it is widely accepted that the stimulation of innate immunity in terms of either gene or protein synthesis, enzyme activity, or cellular response may benefit the organism during pathogen exposure. Immune stimulation frequently involves immune parameters such as a higher number of leukocytes [120,121], increased phagocytic activity [122][123][124], respiratory bursts [122,125], immunoglobulin M (IgM) [126,127], ß-defensins [128], proinflammatory cytokines (interleukin IL-8 and IL-1 β) [124,129], and the modulation of immunity-related genes [129,130]. Probiotics can stimulate elements of the nonspecific immune system, such as mononuclear phagocytes (monocytes, macrophages), neutrophils, and natural killer (NK) cells [131].…”
Section: Health Statusmentioning
confidence: 99%